Blood Glucose Reduction by Combination of Andrographis paniculata (Burm. f.) Ness Herbs and Azadirachta indica A. Juss Leaves in Alloxan-Induced Diabetic Rats - Agung Endro Nugroho, Kurnia Rahayu Purnomo Sari, Anggit Listyacahyani Sunarwidhi, Sudarsono (Journal of Applied Pharmaceutical Science, 2014)
Andrographis paniculata (Burm. f.) Ness and Azadirachta indica A. Juss are Indonesian local plants that are potentially developed as antihyperglycemic agents. This study was aimed to explore antihyperglycemic effect of herbal extract combination of A. paniculata (Burm. f.) Ness and A. indica A. Juss in alloxan-induced rats compared to single extract treatment. Diabetic condition was induced with an intraperitoneal injection of 150 mg/kgBW alloxan monohydrate in the rats. After stable diabetic condition, the rats were administered either with single or extract combination for 15 consecutive days. Blood glucose profiles in both preprandial and postprandial were monitored at the day of 5, 10, and 15. Analysis of blood glucose level was performed using colorimetric method of GOD-PAP. In the study, preprandial and postprandial blood glucose levels of alloxan-induced rats could be decreased after administration of the herbal extract combination of A. paniculata (Burm. f.) Ness and A. indica A. Juss. The extract combination exhibited higher hypoglycemic effects than this of the single extract treatment. In conclusion, the combination of A. paniculata (Burm. f.) Ness and A. indica A. Juss is potential to develop as an antidiabetic agent.
Keywords: Diabetes mellitus, alloxan, Andrographis paniculata and Azadirachta indica.